Türkiye'de Eğitim Bilimleri Alanında Yapılan Karma Yöntem Tezlerde Tipolojik ve Yöntemsel Eğilimler - ÖZDEMİR, ALİ (My University, 2021)
Pozitivist paradigmadan beslenen nicel yöntemler uzun süre bilimsel araştırmalarda tek yöntem olarak kullanılmıştır. Pozitivizme tepki olarak doğan inşacı (yapılandırmacı) ve eleştirel paradigmalar ise nitel yöntemlerin önünü açmıştır. Uzun süre paradigma tartışmalarına maruz kalan bilimsel araştırma dünyası pragmatist felsefenin de etkisiyle karma yöntemi üçüncü araştırma yöntemi olarak kabul etmiştir. Zaman içerisinde farklı araştırmacılar birbirine benzer ve farklı yönler barındıran karma yöntem tipolojileri geliştirmişlerdir. Literatür desteğiyle birlikte karma yöntem araştırmaların özellikle eğitim bilimleri alanında birçok probleme daha kapsamlı çözüm üreteceği söylenebilir. Tarama yöntemiyle gerçekleştirilen bu araştırmada, 2010-2020 yılları arasında eğitim bilimleri temel bilim dallarında karma yöntem kullanılarak yapılan 160 yüksek lisans ve doktora tezi doküman analizi vasıtasıyla incelenmiştir. İlgili tezler yayınlandığı üniversite ve enstitülere, yıllara, karma yöntem tipolojilerine, kullanılan örnekleme yöntemlerine, nicel ve nitel veri toplama ve veri analizi tekniklerine, yaygın yapılan metodolojik hatalara göre incelenerek tezlerdeki tipolojik ve yöntemsel eğilimler ortaya çıkarılmıştır. Araştırma sonucunda doktora düzeyinde yürütülen karma yöntem tezlerinin yüksek lisans düzeyinde yürütülenlere oranla daha fazla olduğu sonucuna ulaşılmıştır. Karma yöntemle yapılan tezlerin yürütüldüğü üniversitelerin başlıca Marmara ve Hacettepe Üniversitesi olduğu, yayınlanan lisansüstü tezlerin önemli bir kısmının eğitim bilimleri enstitülerinde, diğer kısmının ise sosyal bilimler enstitüleri bünyesinde yürütüldüğü sonucuna ulaşılmıştır. Tezlerde en yaygın olarak kullanılan tipolojilerin sırasıyla açımlayıcı ve keşfedici karma yöntem desenleri olduğu görülmüştür. Araştırma sonuçları alan yazındaki benzer çalışmaların bulgularıyla karşılaştırılarak, karma yöntemin eğitim bilimleri alanında daha yaygın kullanımı konusunda önerilere yer verilmiştir.

Quantitative methods influenced by the positivist paradigm have been used as the only method in scientific research for a long time. Constructivist and critical paradigms that emerged as a reaction to positivism paved the way for qualitative methods. Being exposed to paradigm debates for a long time, the community of scientific researchers has accepted the mixed method as the third research method with the influence of the pragmatist philosophy. Over time, different researchers have developed mixed method typologies that incorporate similar and different aspects. With the support of the literature, one can say that research using the mixed method will produce more comprehensive solutions to many problems, especially in the field of educational sciences. In this research carried out by scanning method and document analysis, 160 master's and doctoral theses that used mixed method in educational sciences between 2010 and 2020 were analyzed. Typological and methodological trends in the theses were revealed by examining these theses according to the universities and institutes they were published in, year of publication, mixed method typologies, sampling methods, quantitative and qualitative data collection and data analysis techniques, and common methodological errors. According to the results, it was found that the theses conducted at the doctoral level using the mixed method are more than those conducted at the master's level. It was also found that theses using the mixed method were conducted mainly in Marmara and Hacettepe Universities, and that a significant percentage of the postgraduate theses were conducted in institutes of educational sciences, whereas the others were conducted in institutes of social sciences. Theses employing the mixed method were completed mostly in the curriculum and instruction branch, followed by educational administration and supervision. The results show that the interest in mixed method research has increased in recent years. It was observed that the most commonly used typologies in theses are explanatory, followed by exploratory mixed method designs. In the quantitative parts of mixed studies, mostly survey methods were preferred followed by quasi-experimental methods, while case study and phenomenology were preferred most in qualitative parts. The findings revealed that the most common methodological errors in the theses were that qualitative and quantitative designs were not specified and sampling methods were not explained adequately. Suggestions were made on the more common use of the mixed method in educational sciences by comparing the results of the research with the findings of similar studies in the literature.
TYPOLOGICAL AND METHODICAL TRENDS IN MIXED METHOD THESES IN THE FIELD OF EDUCATION SCIENCES IN TURKEY: A CONTENT ANALYSIS